Knowledge, Attitudes, and Practices in Antibiotic Dispensing amongst Pharmacists in Trinidad and Tobago: Exploring a Novel Dichotomy of Antibiotic Laws - Rajeev P. Nagassar; Amanda Carrington; Darren K. Dookeeram; Keston Daniel; Roma J. Bridgelal-Nagassar (Antibiotics, 2023)
The inappropriate consumption, use, and dispensing of antibiotics are problems faced globally, with a pattern of inappropriate consumption differing in higher-income countries due to the ease of accessibility of antibiotics. The main drivers of consumption and inappropriate use are the over-the-counter sales of antibiotics by pharmacies. Trinidad and Tobago (T&T), a twin island state in the Caribbean, has two Acts of Parliament that regulate antibiotics: the Antibiotics Act and the Food and Drug Act, yet the Over-the-Counter (OTC) sale of antibiotics still exists. This study sought to determine the knowledge, attitudes, and practices regarding the OTC dispensing of antibiotics in T&T. A cross-sectional study gathered data from pharmacists in both the private and public sectors of Trinidad over 7 months. The results showed that antibiotic resistance and antibiotic abuse were seen as significant problems. The level of experience, gender (female), and age (younger) were significantly associated with having good overall knowledge of good dispensing habits and antibiotic laws (p = 0.036, p = 0.047, and p = 0.001, respectively). Pharmacists generally agreed that antibiotics under the Food and Drug Act may have contributed to OTC dispensing in the private sector (p = 0.013) and that all antibiotics should be under the Antibiotic Act (p = 0.002). Additionally, it was found that the dispensing of antibiotics OTC in the private sector (p = 0.006) occurred: without doctors’ advice and without requesting prescriptions; because it was perceived as lawful (especially by older pharmacists); and because of the perceived motivation of profit. Regulation enforcement was perceived as deficient. OTC dispensing for reasons, such as misunderstanding of laws, occurs in T&T.